983PDifferential expression of circulating miR375 and miR371 to detect teratoma and viable germ cell malignancy. (1st October 2019) - Nappi, L; Thi, M; Eigl, B J; Chi, K N; Gleave, M E; So, A; Black, P C; Hamilton, R; Daneshmand, S; Nichols, C R; Kollmannsberger, C K
Abstract: Background: MicroRNAs are examined for clinical utility in active germ cell malignancies (GCM). miR-371a-3p (miR371) has a very high specificity and high sensitivity for the detection of GCM. However, in teratoma neither tissue nor serum/plasma are miR371 positive. miR375 is overexpressed in teratoma tissue, but detectability in blood and its utility is unknown. Methods: GCM patients (pts) enrolled from 10-2016 to 03-2019 in the GU biobank program at British Columbia Cancer were analyzed for plasma miR371/miR375 expression by RT-PCR and quantified by ΔΔCT method. Spike-in cel-miR-39-3p, miR-451 and miR-30b-5p were used as quality/internal controls. Sensitivity, specificity, PPV, NPV, AUC of the ROC of miR375 in detecting teratoma were analyzed. Results: miR375 expression was measured in 69 pts of whom 15 (22%) had pathologically confirmed residual teratoma post-chemotherapy, 4 (6%) residual post-chemotherapy mass without teratoma, 8 (11%) no evidence of residual disease post-chemotherapy, 15 (22%) metastatic seminoma and 27 (39%) CSI with no evidence of tumor. miR375 expression was significantly higher in pts with residual teratoma-post chemotherapy than in non-teratoma (p < 0.0001). Concurrent miR371 and miR375 expression was evaluated in 17 pts with metastatic nonseminoma prior to and post-chemotherapy. miR371 correlated with viable GCM and disappeared after chemotherapy in all but one pt (presenting residual choriocarcinoma). Post-chemotherapy miR375 was unchanged or increased from pre-chemotherapy samples in 85% of pts with pathologically confirmed post-chemotherapy teratoma and remained low in 90% of patients with either complete response or non-teratoma after chemotherapy. Sensitivity of miR375 was 93% (95% CI: 68-99), specificity 75% (95% CI: 43-95), NPV 90% (95% CI 95%: 57-98), PPV 82% (CI 95%: 63-93) and the AUC of miR375 in the post-chemotherapy setting was 0.93 (95% CI: 0.83-1.0; p < 0.0001). Conclusions: miR375 is overexpressed and detectable in the plasma of pts with teratoma while its expression is significantly lower in nonseminoma pts without teratoma or in seminoma. The evaluation of miR371/miR375 may be clinically useful to guide therapeutic decisions (surgery or chemotherapy). Larger studies are warranted. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.